Amplified electrochemiluminescence signals promoted by the AIE-active moiety of D–A type polymer dots for biosensing. Issue 1 (20th November 2019) - Wang, Ziyu; Wang, Ningning; Gao, Hang; Quan, Yiwu; Ju, Huangxian; Cheng, Yixiang
Abstract : Donor-acceptor type conjugated polymers were synthesized to obtain amplified electrochemiluminescence signals promoted by AIE-active moieties. Abstract : Three-component conjugated polymers of a strong donor–acceptor (D–A) type could be synthesized by Pd-catalyzed Suzuki coupling polymerization reaction of 1, 2-bis(4-bromophenyl)-1, 2-diphenylethene (M-1 ) with 9-octyl-3, 6-bis(4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaborolan-2-yl)-9 H -carbazole (M-2 ) and 4, 6-bis(( E )-4-bromostyryl)-2, 2-difluoro-5-phenyl-2 H -1l3, 3, 2l4-dioxaborinine (M-3 ). Among them, P-1 and P-2 with high TPE ratios at 0.95 and 0.9 showed obvious aggregation-induced emission (AIE) behavior; in contrast P-3 with a low TPE ratio at 0.8 showed an aggregation-caused quenching (ACQ) phenomenon. In particular, the three resulting polymer dots (P-1 to P-3 Pdots) exhibited a 200 mV lower electrochemiluminescence (ECL) potential due to their strong D–A electronic structure. Most importantly, the ECL signals of Pdots could be enhanced as high as 3 times by increasing their AIE-active TPE moiety ratios from 0.8 (P-3 ) to 0.95 (P-1 ) via the band gap emission process. Herein, P-1 Pdots with the strongest ECL signal were successfully used as ECL biosensors for the detection of catechol, epinephrine and dopamine with detection limits of 1, 7 and 3 nM, respectively. This work provides a new strategy for developing highly sensitive ECL biosensors by the smart structure design of the AIE-active Pdots.